Left to right the cultural shift from words to pictures - Crow, David 1962- (Laussane, Switzerland Ava Academia, 2006)
The cultural shift from words to pictures is an in-depth study of the influence digital technology has had on the way we communicate, and the increasingly visual nature of our culture.
Title appears as L [arrow] R on t.p.
Title appears as [reverse] R [arrow] L on cover.
Keywords: Visual communications